Aktualisasi Manajemen Berbasis Sekolah (MBS) Berbasis Pendidikan Islam dalam Peningkatan Kualitas Mutu Sekolah - Komara, Endang; Apip, Moch.; Sukamto; Marup (Adabuna : Jurnal Pemikiran dan Pendidikan, 2023)
This research aims to describe the application of the concept of school-based manajement (SBM) as an effort to create superior schools. This is done to build the school's existence in terms of institutional competitiveness and to realize the competitiveness of superior graduates. This research was conducted using research with a qualitative descriptive approach. Data collection was carried out using observation, interviews and documentation methods. Data analysis used after the data is collected is through data reduction, data presentation and drawing conclusions. Based on the results of research conducted, it is hoped that the implementation of SBM can strengthen the participation of all parties in education manajement and create an inclusive, transparent and accountable educational environment in collaboration with all stakeholders. This collaboration aims to improve the quality of education, involving all parties involved and achieving a common goal in creating an SBM concept that is oriented towards superior school quality so that it has an impact on the competitiveness of the graduates produced.